Annual migratory patterns of Long-billed Curlews in the American West. (2nd January 2014) - Page, Gary W.; Warnock, Nils; Tibbitts, T. Lee; Jorgensen, Dennis; Hartman, C. Alex; Stenzel, Lynne E.
Abstract: Effective conservation of migratory species requires comprehensive knowledge of annual movement patterns. Such information is sparse for the Long-billed Curlew ( Numenius americanus ), a North American endemic shorebird of conservation concern. To test hypotheses about individual and area differences in migratory patterns across western North America, we tagged 29 curlews with satellite transmitters at breeding sites in Oregon, Nevada, and Montana. Transmissions from 28 birds for up to 4 years demonstrated that all wintered within the species' known winter range, including 9 from Oregon tracked to agricultural areas of California's Central Valley; 5 from Nevada tracked to the Central Valley, northern Gulf of California, or west coast of Baja California, Mexico; and 14 from Montana that wintered inland, from the Texas Panhandle south to the Mexican Plateau, or near the Gulf of Mexico. Montana breeders migrated east of the Rocky Mountains and traveled more than twice the distance of Oregon and Nevada breeders. Montana birds also stopped more often and longer during most passages. As a group, curlews arrived on their Oregon breeding grounds earlier than in Montana, while males preceded females in Montana and possibly Oregon. No consistent pattern emerged between sexes in departure from breeding areas, although within pairs males departed later than their mates. Individuals exhibited strong fidelity to breeding and wintering sites, and many birds showed a strong propensity for agricultural regions during winter. Our results underscore the importance of studying migration behavior across the breeding range to adequately capture variation in migratory patterns of a species.